The 13th Conference of the International Sports Engineering Association 2020
DOI: 10.3390/proceedings2020049138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rest Periods on Mechanical Ageing of Running Shoes

Abstract: Running is a popular form of exercise, although runners are prone to injury from repeated impact. Running shoes can limit impact forces, but they deteriorate with use. Mechanical ageing typically involves repeatedly compressing the midsole while measuring the energy absorbed within compression cycles to assess degradation. Literature suggests mechanical aging often causes a higher rate of degradation than natural ageing. This work investigated the effect of introducing rest periods into mechanical ageing. Five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Indeed, as evident from the whole graphs of the figure, it is interesting to notice that either the maximal stress, or the residual strain, or the absorbed energy, or the loss coefficient recorded during the interrupted cycling procedure follow those recorded during the continuous one, after a transient period of ≈ 1000 cycles, as if the continuous trends yielded to master curves of the interrupted ones, once a transient regime is achieved. It must be pointed out that similar memory effects were observed by Allen et al regarding the maximum absorbed energy on a 3 consecutive impact fatigue tests of 10000 cycles separated by a 22 h of a rest period [15]. The authors found that after the first resting time, the maximum absorbed energy value was comparable (within measurement error and sample consistency) to those reported at the start of the first ageing period and decrease in a similar manner.…”
Section: Fatigue Testssupporting
confidence: 78%
See 2 more Smart Citations
“…Indeed, as evident from the whole graphs of the figure, it is interesting to notice that either the maximal stress, or the residual strain, or the absorbed energy, or the loss coefficient recorded during the interrupted cycling procedure follow those recorded during the continuous one, after a transient period of ≈ 1000 cycles, as if the continuous trends yielded to master curves of the interrupted ones, once a transient regime is achieved. It must be pointed out that similar memory effects were observed by Allen et al regarding the maximum absorbed energy on a 3 consecutive impact fatigue tests of 10000 cycles separated by a 22 h of a rest period [15]. The authors found that after the first resting time, the maximum absorbed energy value was comparable (within measurement error and sample consistency) to those reported at the start of the first ageing period and decrease in a similar manner.…”
Section: Fatigue Testssupporting
confidence: 78%
“…Analyzing their fatigue (micro)mechanisms represents a challenging task as these systems are sequentially deformed at large cyclic finite strains and exhibit complex compressible elastoviscoplastic behavior [14]. Over the past 40 years, the midsole foams of sport running shoes are mainly made of ethylene-vinyl-acetate (EVA) [15,16], due to their low-cost and their fast and versatile manufacturing process. Thus, if we conducted a preliminary study on other systems such as thermoplastic polyurethane and polyamide-polyether copolymer closed cell foams [17], the fatigue of EVA foams are by far the most studied closed cell foams in the literature [18,19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation